Analysis of Intrinsic Elements in Fairy Tales “Hans im Glück” by Brüder Grimm - Nur Ainun; Syamsu Rijal; Muh. Anwar (Indonesian Journal of Pedagogical and Social Sciences, 2022)
Abstract. This study aims to describe the intrinsic elements in the form of themes, plots, settings, characters, points of view and moral messages in the fairy tale “Hans im Glück” by Brüder Grimm. The research data were taken from the book collection of Brüder Grimm's fairy tales. Data were analyzed based on a qualitative approach with content analysis techniques. The results of the research are as follows, a description of the theme elements: happiness, plot elements: forward plot, background elements: rural setting and summer time, character elements: main and additional characters, point of view elements: using third person point of view called the author's narrator (Auktorialer Erzähler), the element of the moral message: always think positive. The interrelationships between the intrinsic elements of fairy tales include themes, plots, settings, characters, points of view, and moral messages showing a structure that influences each other and cannot be separated. Keywords: intrinsic elements, fairy tales, content analysis.